Impact of cement type and abutment height on pull-off force of zirconia reinforced lithium silicate crowns on titanium implant stock abutments: an in vitro study - Lisa Müller; Angelika Rauch; Daniel R. Reissmann; Oliver Schierz (BMC, 2021)
Abstract Background Pull-off forces of cement-retained zirconia reinforced lithium silicate (ZLS) in implant-supported single crowns on stock titanium abutments with respect to abutment height and implant cement were evaluated and compared. Methods Pull-off force of ZLS crowns on stock titanium abutments was evaluated concerning dental cement and abutment height. A total sample size of 64 stock abutments with heights of 3 mm (n = 32) and 5 mm (n = 32) was used. The ZLS crowns were cemented with four different types of cement (one temporary, two semi-permanent, and one permanent). After cementation, water storage, and thermocycling each sample was subjected to a pull-off test using a universal testing machine. Results The temporary cement showed the least pull-off force regardless of abutment height (3/5 mm: means 6 N/23 N), followed by the semi-permanent methacrylate-infiltrated zinc oxide cement (28 N/55 N), the semi-permanent methacrylate-based cement (103 N/163 N), and the permanent resin composite cement (238 N/820 N). Results of all types of cement differed statistically significantly from each other (p ≤ .012). The type of implant cement has an impact on the pull-off force of ZLS crowns and titanium abutments. Conclusions Permanent cements present higher retention than semi-permanent ones, and temporary cements present the lowest values. The abutment height had a subordinate impact.